Affect and the Judicial Assessment of Offenders: Feeling and Judging Remorse. (June 2015) - Rossmanith, Kate
In most common law jurisdictions worldwide, an offender's remorse is a mitigating factor in sentencing. It matters whether or not a person who has committed a crime is truly sorry for what they have done. And yet how judges evaluate such expressions is unclear. Drawing on 18 interviews with judges in the New South Wales criminal justice system in Australia, this article examines the status of offenders' live, sworn evidence in the judiciary's assessment of offenders' remorse. These interviews with the judiciary reveal that remorse assessment often operates beyond semiotic, representational paradigms (such as 'demeanour assessment') and instead works, in experiential terms, as a feeling. When it comes to offenders getting into the witness box and speaking of their remorse, it seems that sometimes something gets felt by judges at the level of embodied affect that then enables them to declare: 'This person is remorseful.'